Mobility and stress analysis of different surgical simulations during a sacral colpopexy, using a finite element model of the pelvic system. Issue 6 (June 2016) - Jeanditgautier, Estelle; Mayeur, Olivier; Brieu, Mathias; Lamblin, Gery; Rubod, Chrystele; Cosson, Michel
Abstract Introduction and hypothesis We aim to analyze the combined influence of the size of the mesh, the number of sutures, the combined use of an anterior and posterior mesh, and the tension applied to the promontory, on the mobility of the pelvic organs and on the sutures, using a Finite Element (FE) model of the female pelvic system during abdominal sacral colpopexy. Methods We used a FE model of the female pelvic system, which allowed us to simulate the mobility of the pelvic system and to evaluate problems related to female prolapse. The meshes were added to the geometrical model and then transferred to computing software. This analysis allowed us to compare the stress and mobility during a thrust effort in different situations. Results The bigger the mesh, the less mobility of both anterior and posterior organs there would be. This is accompanied by an increase in stress at the suture level. The combination of a posterior mesh with an anterior one decreases mobility and stress at the suture level. There is a particularly relevant stressing zone on the suture at the cervix. The increase in the number of sutures induces a decrease in the tension applied at each suture zone and has no impact on organ mobility. Conclusion Our model enables us to simulate and analyze an infinite number of surgical hypotheses. Even if these results are not validated at a clinical level, we can observe the importance of the association of both an anterior and a posterior mesh or the number of sutures.